2013
DOI: 10.1074/jbc.m113.453951
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Long-range Protein Network That Modulates Active Site Dynamics in Extremophilic Alcohol Dehydrogenases

Abstract: Background:The role of protein flexibility in the C-H activation step, catalyzed by homologous thermophilic and psychrophilic alcohol dehydrogenases, is addressed. Results: Mutation at the substrate-binding site, or at a dimer interface, alters kinetic properties and protein oligomeric structure. Conclusion: Active site flexibility is correlated with subunit interactions 20 Å away. Significance: A long-range network of catalytically relevant, dynamical communication is identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 49 publications
9
69
0
Order By: Relevance
“…Studies of alcohol dehydrogenases have shown that longrange conformation selection is important in catalysis (111). The work presented here suggests that long-range conformational interactions may also play an important role in the PSII reaction center.…”
Section: Discussionmentioning
confidence: 82%
“…Studies of alcohol dehydrogenases have shown that longrange conformation selection is important in catalysis (111). The work presented here suggests that long-range conformational interactions may also play an important role in the PSII reaction center.…”
Section: Discussionmentioning
confidence: 82%
“…As indicated in Figure 9, an Arrhenius plot of the transformed data clearly shows the non-linearity of the rate constant with respect to temperature. Specifically, two transition temperatures are observed, indicating a strong coupling between conformational dynamics and activation energy [48-54]. There are two transition points along the Arrhenius plot, with one around 28.3 °C and another around 34.8 °C.…”
Section: Resultsmentioning
confidence: 99%
“…A convex Arrhenius plot indicates a decreasing activation energy with increasing temperature [51], as is observed for the Mtu RecA mini -intein in the 30.5 °C to 35 °C temperature range. In many cases, the lowest-energy states in enzyme catalysis can be conformationally flexible and are favorable at higher temperatures, leading to observed biphasic rate constants with changes in temperature [48-54]. For example, wild-type tetrameric thermophilic alcohol dehydrogenase from Bacillus stearothermophilus (ht-ADH) has small kink in its Arrhenius plot [54], indicating an obvious yet weak change in activation energy.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the use of a bulky substrate benzyl alcohol in primary H/D substrate kinetic isotope effect (KIE) measurements revealed a “breakpoint” for the temperature dependence, where the KIE was largely temperature independent above 30 °C but increased sharply at lower temperatures 7. Site‐directed mutagenesis and hydrogen–deuterium exchange studies showed that the flexibility of a group of residues greatly affects the temperature dependence of the substrate KIE 6b, 7a,7b,7d. It has been suggested that these residues are responsible for modifying the distance between hydride donor and acceptor 8.…”
mentioning
confidence: 99%